Kajian Kegiatan Sekim Cepat Kaya Di Semenanjung Malaysia - Muhamad Muda; Muhamad Haizuan Rozali; Md. Yunus Abd Aziz (Universiti Sains Islam Malaysia, 2024)
This exploratory study examined the activities of the Get-Rich-Quick schemes in Peninsular Malaysia. Its main objective is to understand how the schemes are operated and to study the activities from the syarak point of view. The focus of the study is to understand the motivations, both the participants as well as the promoter, for them to be involved in such schemes. Using interviews and secondary data, following on the case study approach, the study obtained data pertaining to the types, forms and modus operandi of the schemes. In addition, it also examined the economic and psychological impact on the victims. The data were analysed using the content analysis and grounded hypothesis. Despite it is well-known that the schemes possess the elements of fraud and deceptions, yet many people in many places continued to participate and ended up as victims. They do not only lost money and wealth, but also suffer mental anguish. On the other hand, despite contravening the law and the promoters are punishable severely in the court of law, the activities continued to appear within the society. Many of the victims appear to be more prominent, though not exclusively, in the low income group and from a certain racial group - particularly the Bumiputera. The promoter, however, are of various backgrounds. Due to the existence of fraud and deception elements, the schemes are viewed as haram from the syarak perspective. The main motivation for the respondents to participate in the scheme is the urge to get-rich-quick and the convincing approach made by the promoters. Those whose urge to get rich quick appear as an influence by the existing participants. This factor is exarcebated by lack of knowledge about investments and the element of awe among the victims towards the promoter, whose pursuasive skills are said to be very effective and they also used all possible methods to lure and impress upon the victims, including using religious approach. The study suggests a more aggressive "public education" programmes among the public in order to eradicate the unbecoming activities. This should also include using religious approach. It is also suggested that, a program for creating awareness for proper financial planning among the Bumiputra be created. However, a thorough understanding of the aspiration of the Malays is necessay in order to ensure effectiveness of this programme.